Scientific Literacy of Secondary School Students' Related the Global Warming Subject - Rusilowati, A; Supriyadi; Dwijananti, P; Khabibah, E A N (Journal of physics. Conference series, 2019)
The purposes of this research to describe of scientific literacy of secondary school students related materials of global warming. This research used quantitative descriptive method. The sample research was seventh grade students of secodary school at Central Java, Indonesia. The research instrument used a scientific literacy test in the form of a description that includes four scientific literacy categories that are science as the body of knowledge, science as a way of investigating, science as a way of thinking, and interaction between science, environment, technology, and society. The results showed that the average scientific literacy of students in all categories was 43.39%. Scientific literacy of students in each category obtained a percentage of ≤54% with very less criteria for the science category as a body of knowledge, a way to investigate and a way of thinking. The category of interactions between science, environment, technology, and society is less criteria with average percentage 57.25%. This shows that the scientific literacy skills of SMP and MTs students are still low.